Improving sustainability index through the implementation of total productive maintenance for the bending process in electrical manufacturing - Shumaesi, Rifdah; Safitri, Dian Mardi; Witonohadi, Amal (OPSI, 2025)
The significant losses caused by breakdowns in the bending machine directly affect Company X. Machines that frequently experience breakdowns can also adversely affect machine efficiency due to the need for component replacements, which contradicts the principle of sustainability aligned with the Sustainable Development Goals (SDGs) aimed at achieving a better and more sustainable future for all. The objective of this study is to improve the sustainability index (SI) through Total Productive Maintenance (TPM) and to calculate the Overall Equipment Effectiveness (OEE). These three aspects are closely related to enhancing company productivity in terms of production and sustainability. The study includes calculations of machine effectiveness using OEE and the assessment of company losses using the Six Big Losses framework. The results indicate that the average OEE over one year is 55%, which is below the international ideal standard and the company's target of 70%. Additionally, the sustainability index value obtained is 82.36%. Improvements are proposed based on the pillars of Total Productive Maintenance, focusing on safety, health, and environment, planned maintenance, and autonomous maintenance, all while considering sustainability aspects.  Furthermore, the study suggests enhancements to the 6S foundation within the company, adhering to sustainability aspects in line with SDG 12. By implementing a Total Productive Maintenance strategy that considers Safety, Health, and Environment, Planned Maintenance, and Autonomous Maintenance, and by advancing the 6S concept, the sustainability index value can be increased to 80.91%. Moreover, the effectiveness of the bending machine can be improved to 70.34%.